2002
DOI: 10.1161/01.hyp.0000035856.77718.da
|View full text |Cite
|
Sign up to set email alerts
|

Nonnarcotic Analgesic Use and the Risk of Hypertension in US Women

Abstract: Abstract-Acetaminophen, aspirin, and other nonsteroidal anti-inflammatory drugs (NSAIDs) are widely consumed. Each is theoretically capable of elevating blood pressure by altering prostaglandin homeostasis; however, there is little prospective information on the relation between these agents and physician-diagnosed hypertension. We examined the association between the use of aspirin, acetaminophen, or NSAIDs and incident hypertension in a prospective cohort study of 51 630 women 44 to 69 years of age in 1990 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
2
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 22 publications
2
72
2
3
Order By: Relevance
“…32,33 NSAIDs, in particular, are associated with modest but predictable increases in blood pressure. Meta-analyses of the effects of NSAIDs have indicated average increases in mean arterial pressure of approximately 5.0 mm Hg.…”
Section: Drug-related Causesmentioning
confidence: 99%
“…32,33 NSAIDs, in particular, are associated with modest but predictable increases in blood pressure. Meta-analyses of the effects of NSAIDs have indicated average increases in mean arterial pressure of approximately 5.0 mm Hg.…”
Section: Drug-related Causesmentioning
confidence: 99%
“…Analyses from the Nurses' Health Study (NSH) comparing the highest (>22 days/month) with the lowest (none) exposure group found that increased frequency of use of aspirin, acetaminophen, or NSAIDs, was associated with an increased risk of self reported physician-diagnosed HTN (aspirin, RR = 1.21; 95% CI, 1.13-1.30; acetaminophen, RR = 1.20; 95% CI, 1.08-1.33; NSAIDs, RR = 1.35; 95% CI, 1.25-1.46). 6 A later analysis of the NHS II found similar results for acetaminophen (RR = 2; 95% CI, 1.52-2.62) and for NSAIDs (RR = 1.86; 95% CI, 1.51-2.28), but no significant association was found for aspirin. 5 However, the mean age in this second analysis was lower (range, 31-50) than in the first one (range, 49-61).…”
Section: Discussionmentioning
confidence: 88%
“…4 Results from different prospective studies conducted in the United States assessing the association between use of aspirin, NSAIDs and other analgesics and the risk of hypertension suggest that chronic users of aspirin, NSAIDS, and acetaminophen have a higher risk of hypertension. [5][6][7][8][9] However, some clinical trials conducted in Spain have shown the opposite effect 10,11 and no previous prospective study has assessed this potential relationship in a European cohort, where a different health system probably means different access to medication and a different pattern of drug use. 12 Our objective was to assess the association between regular use of aspirin and non-aspirin analgesic drugs and the incidence of HTN in a prospective dynamic cohort study consisting of Spanish university graduates, the SUN (Seguimiento Universidad de Navarra, University of Navarra Follow-up) project.…”
Section: Assessment Of Incident Hypertensionmentioning
confidence: 99%
“…[5][6][7] In addition, chronic paracetamol consumption maybe related to hypertension, a major vascular risk factor. [8][9][10] Indeed, some studies have shown an increased risk of cardiovascular events and stroke in patients treated with paracetamol, particularly in high-dose users. 10,11 Nevertheless, the hypothesis of a paracetamol-associated cardiovascular risk remains controversial.…”
Section: April 2016mentioning
confidence: 99%